EMPLOYEE ATTENDANCE APPLICATION AT UNIVERSITAS MUHAMMADIYAH SIDOARJO BASED ON WHATSAPP - Rachmadany, Andry (Journal for Technology and Science, 2025)
Objective: Effective employee attendance management is crucial for optimizing operational efficiency in higher education institutions. This study aims to develop a WhatsApp-based attendance system to enhance accuracy, efficiency, and accessibility at Muhammadiyah University of Sidoarjo. Method: A web-based application was designed and integrated with the WhatsApp API, enabling employees to record attendance by sending messages via WhatsApp. The system includes automated data processing features for administrative monitoring. The research follows a system development life cycle (SDLC) approach, incorporating requirements analysis, design, implementation, and evaluation phases. Results: The implementation of the system demonstrated improved attendance efficiency, minimized human error in data recording, and reduced reliance on additional applications. The administrative panel facilitated real-time monitoring, enhancing managerial oversight. Novelty: This study presents an innovative approach by leveraging WhatsApp—a widely used communication platform—as a cost-effective alternative to conventional attendance systems. The integration of WhatsApp API eliminates the need for dedicated mobile applications, reducing maintenance costs and improving user adoption. This solution offers a practical model for universities seeking to modernize attendance management while maintaining ease of use for employees.